2021
DOI: 10.1016/j.ijid.2021.03.074
|View full text |Cite|
|
Sign up to set email alerts
|

Hospitalization of mild cases of community-acquired pneumonia decreased more than severe cases during the COVID-19 pandemic

Abstract: Objective The epidemic of the coronavirus disease 2019 (COVID-19) has affected the entire health care systems. Our aim was to assess the impact of the COVID-19 epidemic on the number and severity of cases for community-acquired pneumonia (CAP) in Japan. Methods Using claims data from the Quality Indicator/Improvement Project (QIP) database, we included urgent cases of inpatients for CAP from August 1, 2018, to July 30, 2020. We compared the monthly ratio of inpatient ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…However, the COVID-19 pandemic onset will probably represent an inflection point for the incidence of CAP cases unrelated to SARS-CoV-2. Indeed, during the first waves of the COVID-19 pandemic, lower rates of admission for CAP have been reported, mainly in milder cases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the COVID-19 pandemic onset will probably represent an inflection point for the incidence of CAP cases unrelated to SARS-CoV-2. Indeed, during the first waves of the COVID-19 pandemic, lower rates of admission for CAP have been reported, mainly in milder cases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [6] suggested that the reduced volume of ICU patients was due to patients’ hesitancy to visit hospitals. In fact, a reduction in case volumes has been observed in many areas, including acute coronary syndrome[22], pneumonia[23], and surgeries[24]. However, the reasons behind the reduction in admissions have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Since the treatment of COVID-19 patients is considered to exhaust the capacity to undertake MV[4], MVs are supposed to have been suppressed more than other treatments. However, changes in patient volumes have been reported in various areas, including acute coronary syndrome[22], pneumonia[23], and surgeries[24]; the influence of these changes cannot be denied. In addition, volumes themselves of respiratory infection diseases were suggested to decrease due to infection prevention measures employed by residents during the epidemic of the COVID-19[23, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, there was a marked reduction in the number of inpatients with non‐COVID‐19 acute respiratory infections during the COVID‐19 pandemic. 32 , 33 Therefore, this factor could be a contributor to reducing infection‐related hospital admissions of HF patients. Furthermore, because medical resources were transferred to prioritize COVID‐19 patients, there may have been delays in the treatment of less urgent HF patients.…”
Section: Discussionmentioning
confidence: 99%